人工智能对共同希望语言学院2023届第六学期晚班学生汉语能力提升的影响分析 - Angelica Mei Sari; Ricky Wijaya; Louis Saviola; Refky Refky; Syafahrudin Syah; Theresia Fitri; Sabinus Iden (Journal of Maobi, 2026)
With the advancement of digital technology, the use of Artificial Intelligence (AI) as a learning medium has become increasingly common in the field of education. Mandarin language students employ AI for various purposes, such as checking grammar, practicing speaking, searching for materials, completing assignments, and asking questions. Therefore, this study aims to analyze the impact of AI usage in improving Mandarin language proficiency among sixth-semester evening class students of the 2023 cohort. The research seeks to determine the extent to which AI contributes to enhancing students’ Mandarin language skills. The research method involved collecting data through questionnaires and interviews. The study involved 18 sixth-semester evening class students from the 2023 cohort who used AI-based learning applications in their Mandarin learning process. The findings indicate that the use of AI can help improve Mandarin proficiency, particularly in vocabulary comprehension, grammar, and pronunciation. Based on these results, it can be concluded that AI has a positive influence on enhancing Mandarin language skills and comprehension. It can serve as a practical and easily accessible alternative learning medium. However, it should still be complemented with conventional teaching methods to ensure students achieve more optimal outcomes.